Maintenance of high proteolipid protein level in adult central nervous system myelin is required to preserve the integrity of myelin and axons. Issue 4 (14th January 2019) - Lüders, Katja A.; Nessler, Stefan; Kusch, Kathrin; Patzig, Julia; Jung, Ramona B.; Möbius, Wiebke; Nave, Klaus‐Armin; Werner, Hauke B.
Abstract: Proteolipid protein (PLP) is the most abundant integral membrane protein in central nervous system (CNS) myelin. Expression of the Plp ‐gene in oligodendrocytes is not essential for the biosynthesis of myelin membranes but required to prevent axonal pathology. This raises the question whether the exceptionally high level of PLP in myelin is required later in life, or whether high‐level PLP expression becomes dispensable once myelin has been assembled. Both models require a better understanding of the turnover of PLP in myelin in vivo. Thus, we generated and characterized a novel line of tamoxifen‐inducible Plp ‐mutant mice that allowed us to determine the rate of PLP turnover after developmental myelination has been completed, and to assess the possible impact of gradually decreasing amounts of PLP for myelin and axonal integrity. We found that 6 months after targeting the Plp ‐gene the abundance of PLP in CNS myelin was about halved, probably reflecting that myelin is slowly turned over in the adult brain. Importantly, this reduction by 50% was sufficient to cause the entire spectrum of neuropathological changes previously associated with the developmental lack of PLP, including myelin outfoldings, lamellae splittings, and axonal spheroids. In comparison to axonopathy and gliosis, the infiltration of cytotoxic T‐cells was temporally delayed, suggesting a corresponding chronology also in the genetic disorders of PLP‐deficiency. High‐level abundance of PLP in myelin throughout adult life emerges as a requirement for the preservation of white matter integrity. Main Points: The SPG2 disease gene Plp is deleted in adult mice. Abundance of PLP in CNS myelin is halved 6 months later, reflecting its slow turnover. This suffices to impair myelin and axon integrity. High PLP‐content of myelin is subject to selective pressure.